Proceedings of the 26th ACM International Conference on Multimedia 2018
DOI: 10.1145/3240508.3240691
|View full text |Cite
|
Sign up to set email alerts
|

Slions

Abstract: Singing songs can be an engaging and effective activity when learning a foreign language. In this paper, we describe a multi-language karaoke application called SLIONS: Singing and Listening to Improve Our Natural Speaking. When developing this application, we followed a user-centered design process which was informed by conducting interviews with domain experts, extensive usability testing, and reviewing existing gamified karaoke and language learning applications. The key feature of SLIONS is that we used au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In Danowska-Florczyk and Motowski [69], the Polish language is taught as a user role-based game, in which its complex grammar system and lexical problems are presented to learners as tasks and activities. There are other innovative ways of pronunciation teaching with gamification, such as a multi-language karaoke application, SLIONS [70], or a recursive dialogue game for personalized pronunciation training [71].…”
Section: B Learning Digital Games and Gamification On Computer-assismentioning
confidence: 99%
See 1 more Smart Citation
“…In Danowska-Florczyk and Motowski [69], the Polish language is taught as a user role-based game, in which its complex grammar system and lexical problems are presented to learners as tasks and activities. There are other innovative ways of pronunciation teaching with gamification, such as a multi-language karaoke application, SLIONS [70], or a recursive dialogue game for personalized pronunciation training [71].…”
Section: B Learning Digital Games and Gamification On Computer-assismentioning
confidence: 99%
“…Most of the time, however, the result is a simple binary output, reporting whether the user correctly performed or failed the activity [69], [73], [74]. In Murad et al [70], an overall score (0 to 100) from a user's karaoke performance is shown to the learner. In the ''Say It Again, Kid!''…”
Section: B Learning Digital Games and Gamification On Computer-assismentioning
confidence: 99%
“…In [118], a CAPT game for practicing Dutch oral and grammar skills based on speaking practice and feedback is reported. There are other innovative ways of pronunciation teaching with gamification, such as a multi-language karaoke application, SLIONS [151] or a recursive dialogue game for a personalized pronunciation training [152]. The previously mentioned studies and applications share game design elements which can be classified into [153]:…”
Section: Gamification and L2 Pronunciation Trainingmentioning
confidence: 99%
“…In particular for pronunciation training, this important resource could be used to assess the goodness of the user interaction and to measure the user proficiency [150], [154], [155]. For instance, in [151], an overall score (0 to 100) from a user's karaoke performance is shown to the learner. Besides, points can involve the accomplishment of user's levels and badges and can lead to earning rewards in Duolingo and Babbel.…”
Section: Gamification and L2 Pronunciation Trainingmentioning
confidence: 99%
See 1 more Smart Citation